Kampo Medicine for Various Aging-Related Symptoms: A Review of Geriatric Syndrome - Takayama, Shin; Tomita, Naoki; Arita, Ryutaro; Ono, Rie; Kikuchi, Akiko; Ishii, Tadashi (Frontiers in Nutrition, 2020)
With continued growth of the aging population in Japan, geriatric syndrome (GS), which is associated with aging-related symptoms, has become a social problem. GS is caused by physiological and pathological aging and may manifest various symptoms. Physicians use multidisciplinary approaches to provide treatment for individual GS symptoms. Kampo medicine, a Japanese traditional medicine that uses multiple pharmacologically active substances, is useful for many syndromes, conditions, disorders, and diseases associated with GS. Evidence of the effectiveness of Kampo medicine for GS has accumulated in recent years. The effects of Kampo treatment for symptoms related to functional decline of the cardiovascular, respiratory, and digestive systems, cognitive impairment and related disorders, pain and other sensory issues, among others, support the use of Kampo medicine for the management of GS. The role of Kampo medicine for GS is summarized in this review.